Sindrom Serotonin - Dewi Nur Fiana; Raisha Rahmani Rizal (CV. Jasa Sukses Abadi, 2021)
Serotonin (SS) syndrome (also referred to as serotonin toxicity) is a potentially life-threatening drug-induced toxidrome associated with increased serotonergic activity in the peripheral (PNS) and central nervous system (CNS). It is characterized by a dose-relevant spectrum of clinical findings associated with levels of free serotonin (5-hydroxytryptamine [5-HT]), or activation of 5-HT receptors (especially the 5-HT1A and 5-HT2A subtypes), which include neuromuscular disorders, autonomic hyperactivity, and altered mental states. Serotonin toxicity begins within a few hours of taking a drug that causes an increase in serotonin. The three classic sets of clinical features are neuromuscular excitation (eg, clonus, hyperreflexia, myoclonus, rigidity), autonomic nervous system excitation (eg, hyperthermia, tachycardia), and altered mental state (eg, agitation, confusion). Although serotonin syndrome rarely causes death, severe cases are medical emergencies that can rapidly lead to multisystem organ failure. Although many drugs have been implicated in serotonin syndrome, life-threatening cases generally occur only when a monoamine oxidase inhibitor is combined with a selective serotonin re-uptake inhibitor. or non-selective. Awareness of Serotonin Syndrome is critical not only in avoiding inadvertently harmful combinations of therapeutic drugs but also in recognizing the clinical picture when it occurs so that treatment can be started immediately. Doctors and nurses should be aware of serotonin syndrome because drugs that can cause it are often used, and intentional overdoses with drugs that can cause serotonin syndrome are seen with increasing frequency. This makes it difficult to detect and doctors can easily mistake serotonin syndrome for antoher diagnose. In this review, the pathophysiology, clinical features, drugs involved and diagnosis of serotonin syndrome are discussed.